INSTAGRAM : A MEDIUM IN IMPROVING STUDENTS’ WRITING - Lambok Hermanto Sihombing; Puji Lestari (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2022)
Instagram is a popular social media among young people, particularly students. It can be used for students to share their most memorable moments and improve their writing skills. The students may compose a narrative and publish it on Instagram. The teacher can then evaluate their creative writing. This study aims to analyze how Instagram digital poster projects can help students improve their writing skills. To support this analysis, the researchers utilized a qualitative methodology and applied the Teaching by Principle theory by H. Douglas Brown and Heekyong Lee and the New Media theory by J. Van Dijck and T. Poell. The scope of the study was derived from the writing of SMK Binakarya Mandiri Bekasi students and some supporting articles. There were three participants included in this study. This study's findings show that students can improve creative digital poster project on their Instagram accounts.